1972
DOI: 10.1093/bja/44.7.712
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Levels in Children During Surgery

Abstract: Changes in blood glucose levels in children during surgery have been found not to follow the pattern reported in adults, no relationship being found between the "stressfulness" of the operation and the rate of rise of blood glucose concentration. In 10 per cent of the children studied the blood glucose level immediately after induction was within the hypoglycaemic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 2 publications
(4 reference statements)
0
18
0
2
Order By: Relevance
“…[2][3][4] Although several clinicians have reported maintenance of normoglycaemia preoperatively, and hyperglycaemic response to surgery and anaesthesia in healthy children in spite of fasting; [5][6][7][8][9][10][11][12][13][14] others have observed hypoglycaemia in a significant minority. [3,[15][16][17][18][19][20][21][22][23] Failure to demonstrate hyperglycaemia or outright hypoglycaemic response to anaesthesia and surgery has been reported by a few. [19,24] A high incidence of preoperative hypoglycaemia was observed among low percentile weight children (40%) by Ilori et al [3] Hypoglycaemia could be a cause of significant morbidity and mortality in the perioperative periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Although several clinicians have reported maintenance of normoglycaemia preoperatively, and hyperglycaemic response to surgery and anaesthesia in healthy children in spite of fasting; [5][6][7][8][9][10][11][12][13][14] others have observed hypoglycaemia in a significant minority. [3,[15][16][17][18][19][20][21][22][23] Failure to demonstrate hyperglycaemia or outright hypoglycaemic response to anaesthesia and surgery has been reported by a few. [19,24] A high incidence of preoperative hypoglycaemia was observed among low percentile weight children (40%) by Ilori et al [3] Hypoglycaemia could be a cause of significant morbidity and mortality in the perioperative periods.…”
Section: Introductionmentioning
confidence: 99%
“…These include 5%, 2.5%, 2%, and 1%. [14][15][16][17][18][19][20][21][22][23][24] However, these are not commercially available in many centres in the sub-Sahara and the pharmacy departments may not be adequately equipped to handle production of these fluids. Currently 4.3% dextrose in 0.18% saline (DS) is the fluid being used in many centres in Nigeria for paediatric perioperative fluid management.…”
Section: Introductionmentioning
confidence: 99%
“…The patients with these low levels did not show any clinical signs suggestive of hypoglycaemia but it seems undesirable that patients about to be subjected to the added stress of an anaesthetic and operation should come in such a physiological state. During operation there is a rise in the plasma glucose level in the normal adult but it has been shown that children do not respond with a hyperglycaemic reaction to the same degree (Watson, 1972;Clarke, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] However, prolonged fasting in children is known to cause hypoglycemia, with reports of fasting glucose as low as 10 mg/dL (0.56 mmol/L). 10,11 Finally the risk of clonidine unmasking a seizure disorder is questionable, supported by a single report. Seizures have not been reported as a part of clonidine overdose or as an adverse event from therapeutic use.…”
Section: Replymentioning
confidence: 99%